(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Late preterm babies, born between 34 and 36 weeks of gestation, are susceptible to mild visual and neurobehavioral problems because they undergo a vital phase of visual system development outside the intrauterine environment. This study aims to evaluate the effectiveness of visual stimulation in late preterm newborns. Case description and management: A 4-month-old child was brought by the parent with complaints of reduced visual tracking and fixation. Clinical findings met ICD-10 criteria for late preterm birth, a disorder related to neurological and sensory system immaturity. The infant received four sessions per week for 4 weeks, each lasting approximately 5–10 minutes. The intervention included black-and-white cards, toy or rattle tracking, dim light tracking, and high-contrast geometric patterns. Baseline assessment using the Hammersmith Infant Neurological Examination (HINE) and the Visual Tracking Assessment revealed reduced neurobehavioral organisation and poor visual tracking, with scores of 23/78 on HINE and 6 on the visual tracking assessment. Following four weeks of visual stimulation intervention, the scores improved to 51/78 on the HINE and 14 on the visual tracking assessment, indicating improved visual fixation, tracking, and neurobehavioral response. Conclusion: This case demonstrates that visual stimulation can effectively enhance visual fixation and tracking in preterm newborns, thereby improving overall well-being.